2019
DOI: 10.1007/s42452-019-0868-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity characteristics of lateritic soil treated with Sporosarcina pasteurii in microbial-induced calcite precipitation application

Abstract: The plasticity characteristics of lateritic soil with varying Sporosarcina pasteurii (S. pasteurii) suspension density and compositional variables were evaluated in microbial-induced calcite precipitation (MICP) application. The liquid limit value of the natural lateritic soil was used to prepare samples with three mix proportions of the bacteria and cementation reagent (i.e., 25% bacteria-75% cementation reagent, 50% bacteria-50% cementation reagent and 75% bacteria-25% cementation reagent). The S. pasteurii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 56 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…This finding was contradicted by Chittoori [138], who reported an increase in both the liquid limit and plasticity index of two clay soils and recorded a substantial reduction in the one-dimensional swell strain after bacterial treatment, with corresponding calcite content of 1.60% and 0.90%. Similarly, studies conducted by Osinubi [139] on lateritic soil after varying the ratio of bacteria to cementation reagent showed that an optimal improvement of plasticity index was achieved for specimens prepared with 75% S. pasteurii and 25% cementation reagent at S. pasteurii suspension density of 2.40 × 10 9 cells/ml, with a peak calcite content of 6.0%. This was due to the higher suspension density of S. pasteurii that were available to maximally hydrolyze the urea within the cementation reagent.…”
Section: Figmentioning
confidence: 83%
See 1 more Smart Citation
“…This finding was contradicted by Chittoori [138], who reported an increase in both the liquid limit and plasticity index of two clay soils and recorded a substantial reduction in the one-dimensional swell strain after bacterial treatment, with corresponding calcite content of 1.60% and 0.90%. Similarly, studies conducted by Osinubi [139] on lateritic soil after varying the ratio of bacteria to cementation reagent showed that an optimal improvement of plasticity index was achieved for specimens prepared with 75% S. pasteurii and 25% cementation reagent at S. pasteurii suspension density of 2.40 × 10 9 cells/ml, with a peak calcite content of 6.0%. This was due to the higher suspension density of S. pasteurii that were available to maximally hydrolyze the urea within the cementation reagent.…”
Section: Figmentioning
confidence: 83%
“…A microorganism can be used for remediation of contaminants if it possesses any of the following characteristics: the ability to utilize, transform, degrade, or grow in the presence of the contaminants, thus toxicity testing is essential, as reported in Ref. [139]. Note that some of these contaminants are essential for cell growth, although they may be toxic at high concentrations due to serious health-related issues.…”
Section: Remediation Of Contaminantsmentioning
confidence: 99%
“…Also, the free passage of microorganisms through the limited pore-throat size remains a challenge in treating the very fine soils using MICP [14]. Recently, researchers have started to focus on assessing the performance of MICP in residual soils that consist fine to coarse grains distributed naturally [14][15][16]. However, only a very limited MICP studies on residual soils have been reported in the literature to the date, providing insufficient information on their mechanical responses.…”
Section: Introductionmentioning
confidence: 99%
“…The swell pressure has been reduced up to 41 kPa for natural soil and 15 kPa for artificial soil. The MICP treatment procures the calcite content, which creates the bond between the soil grains and the formation of the biofilm also increased the barrier between water and clay particles 53 , 54 . And for the artificial soil BC-1 + 30%BA, BC-2 + 30%BA and BC-3 + 30%BA, the swell pressure has been reduced to 48 kPa, 43 kPa, and 39 kPa %, respectively.…”
Section: Resultsmentioning
confidence: 99%